Efeitos de 10 semanas de treinamento com kettlebell na aptidão aeróbica de mulheres jovens saudáveis - Zimerer, Carla (2022)
Kettlebell high-intensity interval training (HIIT) protocols could be an affordable alternative for improving physical fitness in sedentary women. However, further research is needed on the benefits of this method in aerobic fitness. Therefore, the present study aimed to evaluate the effects of kettlebell HIIT on aerobic fitness and muscle strength in healthy young women. Participants were assigned to training (KB: n = 10; age = 25.5 ± 2.75 years; height = 163.0 ± 5.56 cm) or control group ( CG: n = 9; age = 21.00 ± 1.50 years; height = 160.50 ± 5.71). The kettlebell training program (10 weeks) was divided into three phases: phase I (two weeks), phase II (four weeks), and phase III (four weeks). Maximum oxygen consumption (V̇O 2 max), ventilatory threshold 1 (LV 1 ) and ventilatory threshold 2 (LV 2 ) were evaluated during the pre-training (PRE), mid-training (MIDDLE) and post-training (POST) periods. Maximum muscle strength (1RM) and anthropometric measurements were measured PRE and POST. The KB presented significantly higher values than the GC in the POST (p = 0.017; ES = 0.06). Kettlebell high-intensity interval protocol significantly increased velocity associated with V̇O 2 max (vV̇O 2 max: p < 0.001; ∆% = 13.21; ES = 0.17), velocity associated with LV 1 (vLV 1 : p = 0.002, ∆% = 24. 49; ES = 0.18), percentage of heart rate at LV 1 (%HRmax at LV 1 : p = 0.021, ∆% = 14.08; ES = 0.20), oxygen consumption at LV 1 (V̇O 2 at LV1: p = 0.047, ∆% = 33.94; ES = 0.07), velocity associated with LV 2 (vLV 2 : p = 0.005, ∆% = 15.12; ES = 0.16), percentage of heart rate in LV 2 (%HRmax at LV 2 : p = 0.011, ∆% = 7.75; ES = 0.25), oxygen consumption in LV 2 (V̇O 2 at LV 2 : p = 0.035, ∆% = 11.68; ES = 0.04) in POST. There was a significant reduction in V̇O 2 max for the CG between MIDDLE and POST (p = 0.035, ∆%= - 4.70; ES = 0.02). In conclusion, the kettlebell high-intensity interval training program can be a time-efficient and low cost alternative to improve aerobic capacity and muscle strength in sedentary young women.